The effect of hypoxia on protein phosphatase 2A (PP2A) in MDA-MB-231 cells, and, a pilot study to establish a primary breast cancer cell model from Fine Needle Aspirations. - Patten, Victoria Alexandra (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.